Two decades of active layer thickness monitoring in northeastern Asia. (3rd July 2021) - Abramov, Andrey; Davydov, Sergey; Ivashchenko, Andrey; Karelin, Dmitry; Kholodov, Alexandr; Kraev, Gleb; Lupachev, Alexey; Maslakov, Alexey; Ostroumov, Vladimir; Rivkina, Elizaveta; Shmelev, Denis; Sorokovikov, Victor; et al.
ABSTRACT: This study summarizes seasonal thawing data collected in different permafrost regions of northeast Asia over the 1995–2018 period. Empirical observations were undertaken under the Circumpolar Active Layer Monitoring (CALM) program at a range of sites across the permafrost landscapes of the Yana-Indigirka and Kolyma lowlands and the Chukotka Peninsula, and supplemented with 10 years of observations from volcanic mountainous areas of the Kamchatka Peninsula. Thaw depth observations, taken using mechanical probing at the end of the thawing season, and ground temperature measurements, were analyzed with respect to air temperatures trends. The data from 24 sites (16 in the Indigirka-Kolyma region, 5 in Chukotka and 3 in Kamchatka) reveal different reactions of the active layer thickness (ALT) to recent changes in atmospheric climate. In general, there is a positive relation between ALT and summer air temperatures. Since the early 2000s positive ALT anomalies (compared with mean data from all sites) prevail in the Kolyma and Chukotka area, with only one alas site showing a negative ALT trend. The only active site in the Kamchatka Mountains shows no significant thaw depth changes over the period of observation. Two other Kamchatka sites were affected during a volcanic eruption in 2012.